THE CONCEPT OF BRAHMAN AND THE ISSUE OF RELIGIOUS TOLERANCE IN THE PHILOSOPHY OF SARVEPALLI RADHAKRISHNAN - Qorakoz Tolanboyeva Mukhtorjon qizi,Jasur Sulaymonov Baxtiyorovich (International Journal of Literature and Language Studies, 2026)
This article examines the concept of Brahman, which occupies an important place in the philosophical thought of the prominent Indian philosopher Sarvepalli Radhakrishnan, within the framework of the Neo-Vedanta system. It also analyzes the differences in the interpretation of this concept between Radhakrishnan’s philosophy and the classical Vedantic tradition. At the same time, the article discusses the issue of religious tolerance in the philosopher’s thought, as well as the forms in which religious unity is manifested.